IMPLEMENTASI SISTEM ABSENSI PEGAWAI MENGGUNAKAN MAC ADDRESS SMARTPHONE DENGAN SENSOR BLUETOOTH BERBASIS MIKROKONTROLLER ARDUINO - Siti Nur Azizah (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Yudharta Pasuruan)
Along with the development of increasingly advanced technology and the use of hardware in a variety of work activities supported by various software, so that entrepreneurs of a company or agency use the technology as a tool attendance attendance that helps in the assessment and assessment of employee work. This research was conducted to design an attendance attendance system using microcontroller-based Bluetooth sensor that is easy, effective, efficient, and aimed to control and detect sensor, because it uses Bluetooth network as connectivity between hardware module which will produce attendance attendance system. In the Hardware Module originates from the Bluetooth mobile phone that will be connected to the Bluetooth HC-05 module, then Bluetooth Module HC-05 will send commands to detect sensors through Pin that is connected with Arduino Nano and processed into the PC. The result of this research is Bluetooth connection can be used as a tool of attendance by using hardware module connected to PC. Keywords: Bluetooth Mobile, Microcontroller, Bluetooth Sensor HC-05.